CIVIL SOCIETY AND PROBLEMS OF FORMATION OF CITIZENSHIP IN MODERN UKRAINE - Довбня, О.М.; Довбня, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
At the time of emergence of statehood – the important thing is converting the population from subjects to active citizens, who participate in creation of their country and feel proud of independence to their political nation. The barriers on the path to process of formation of civil society and the possibilities of their overcome are researched.